Analisis pendapatan pekerja sektor informal disekitar objek wisata jembatan pendestrian kawasan objek wisata menara Gentala Arasy Kota Jambi - Syahdan Fathiri; Zulfanetti Zulfanetti (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2021)
The purpose of this study was to determine the socio-economic characteristics of traders around the tourist attraction of the pedestrian bridge, to determine the potential and strategies of tourism development, and to determine differences in income from the informal sector. The data used in this study is primary data consisting of interview data. The method used for this research is a field research method with observation techniques and conducting interviews, and distributing questionnaires. The results showed that the variables of age, amount of savings, number of dependents, transportation expenses, and number of tourist visits had a significant effect. However, partially the number of dependents and the number of tourist visits significantly affect the income of informal sector workers around the Pedestrian Bridge Tourism Object in the Gentala Arasy Tower Tourism Object, Jambi City.  Keywords: Income, Informal sector workers, Tourist attraction